Comparison of vancomycin assays in patients undergoing hemodialysis - Letícia Scribel; Aline Galiotto; Isadora de Souza Rodrigues; Roberta Hahn; Rafael Linden; Alexandre P. Zavascki (Brazilian Journal of Infectious Diseases)
Vancomycin is a glycopeptide antibiotic mainly excreted by glomerular filtration. Therefore, patients undergoing hemodialysis tend to accumulate its crystalline degradation product, which has been associated with cross-reaction in commercial immunoassays. The aim of this study was to assess the performance of two commercial immunoassays for measuring vancomycin levels in patients undergoing hemodialysis. This method-comparison study enrolled patients undergoing hemodialysis at two hospitals in Porto Alegre, Brazil. Vancomycin serum concentrations measured by Chemiluminescent Microparticle Assay (CMIA) and measured by Kinetic Interaction of Microparticles in Solution (KIMS) were compared with Liquid Chromatography coupled with Tandem Mass Spectrometry (LC-MS/MS). A total of 64 samples from 42 patients and 54 samples from 23 patients were included in CMIA and KIMS groups. Both measurements were highly correlated with LC-MS/MS, with Spearman rank correlation coefficient r = 0.840 (p < 0.001) and r = 0.926 (p < 0.001), respectively. No deviation of linearity was observed (p = 0.81 and p = 0.49, respectively). The mean difference between CMIA and LC-MS/MS was -1.19 μg/mL and between KIMS and LC-MS/MS was -2.28 μg/mL. LC-MS/MS measured levels were, on average, 2.64 % higher than CMIA and 8.81 % higher than KIMS. CMIA and KIMS revealed accurate commercial methods to measure vancomycin serum concentrations in patients undergoing hemodialysis.